2022
DOI: 10.1136/bmj.o1653
|View full text |Cite|
|
Sign up to set email alerts
|

Smell and taste dysfunction after covid-19

Abstract: The sense of smell is an ancient and vital perception in mammals, with the olfactory receptor gene family making up 1% of the mammalian genome, and the human olfactory system being able to discriminate among thousands of airborne chemicals at concentrations below the detection limits of the most complex analytical systems. 1 However, people only realise the importance of smell when it is lost. The covid-19 pandemic has put both smell and taste disturbances in the spotlight because of the functional impact and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 15 publications
0
28
0
2
Order By: Relevance
“…Viral load is another important parameter to know ( Table 2 ) [ 16 ] for whether people can develop post-COVID-19 symptoms. Our results show that, at a low Ct value [ 15 , 16 , 17 , 18 , 19 , 20 ], patients have between 15 to 20 post-COVID-19 symptoms; likewise, this is reflected when analyzing patients who had an intermediate Ct [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] who presented between 6 to 11 symptoms, and, finally, there were patients with a low Ct [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] who had few or no symptoms ( Figure 3 A). Therefore, a Pearson correlation was performed between the Ct value and the number of post-COVID-19 symptoms (r = 0.…”
Section: Resultsmentioning
confidence: 66%
“…Viral load is another important parameter to know ( Table 2 ) [ 16 ] for whether people can develop post-COVID-19 symptoms. Our results show that, at a low Ct value [ 15 , 16 , 17 , 18 , 19 , 20 ], patients have between 15 to 20 post-COVID-19 symptoms; likewise, this is reflected when analyzing patients who had an intermediate Ct [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] who presented between 6 to 11 symptoms, and, finally, there were patients with a low Ct [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] who had few or no symptoms ( Figure 3 A). Therefore, a Pearson correlation was performed between the Ct value and the number of post-COVID-19 symptoms (r = 0.…”
Section: Resultsmentioning
confidence: 66%
“…While the importance attributed to chemical senses is highly variable [ 33 , 34 ], the COVID-19 pandemic has put them in the spotlight due to the negative impact linked to their alteration or loss and the high prevalence of long-term dysfunctions [ 35 , 36 ]. A meta-analysis by Tan et al [ 14 ] highlighted the severity of long-term self-reported smell and taste alterations in individuals with COVID-19, with about 5% of patients developing persistent alterations, considering data from 3699 patients in 18 studies.…”
Section: Discussionmentioning
confidence: 99%
“…Olfactory training has been shown to be the only disease-specific intervention with evidence of efficacy for the treatment of postinfectious olfactory dysfunction. Treatment based on sniffing and trying to identify scents, such as rose, eucalyptus, lemon, and clove, over the course of several months should be implemented as soon as possible [21].…”
Section: Memory Storagementioning
confidence: 99%